The influence of zinc deficiency on chronic pain in Sprague Dawley rats (Medical Journal of Indonesia, 2010)
Aim Zinc (Zn) deficiency remains a problem in most developing countries, including Indonesia, especially in the East Nusa Tenggara (NTT) Islands. Zinc plays a major role in pain through the modulation process by the N-methyl-Daspartate (NMDA) receptors, which also includes neuronal nitric oxide synthase (nNOS) as a pain parameter. The purpose of this study is to reveal the effects of Zn towards pain response and modulation stage at the spinal cord level in rats. Methods Twenty Sprague Dawley (SD) rats were divided into two groups, a deficient group and a normal group. The deficient group was fed on an IRI-OB diet. Every group was further divided into two more groups, the acute pain group (transient noxious stimuli), and the chronic pain group (continuous noxious stimuli). The rats in chronic pain group were subjected to CCI Bennet operation. The pain thresholds in the deficient group and normal group were measured clinically using a modified Ugo Basille plantar test (thermal transient noxious stimuli). Measurement of chronic pain level was carried out by measuring the nNOS level by immunohistochemistry. Results Deficient group showed an insignificant decrease in pain threshold (P= 0.251). However, there is a significantÂ increase in nNOS (P= 0.027) especially in the deficient group with continuous noxious stimulation. Conclusions These results suggest that Zn deficiency increases pain response, especially in chronic pain. (Med J Indones 2010; 19:88-95)